"No! You can't have it": Problematizing choice in institutionalized adults with intellectual disabilities. (March 2020) - Johnson, Khalilah R; Bagatell, Nancy
Institutionalized adults with profound intellectual disabilities (ID) face significant challenges to having their choice-making cultivated and supported. Based on observational and interview data from an institutional ethnographic study, this article explores how choice-making during mealtimes is acknowledged and problematized by staff. First, we suggest that Foucauldian problematization offers a lens through which to better understand how mealtime intervention plans passed down over time become embodied restrictive practices. Second, we provide examples and analyses of mealtime negotiations between staff and residents. Analyses revealed staff infantilize and misrepresent residents' choice-making during meals as manipulation; additionally, analyses suggest that past experiences of staff with residents and historical meal plans color how they acknowledge and interpret residents' choices. Our argument is an attempt to move forward discussions concerning the implementation of quality habilitation services by highlighting the ways contemporary institutional systems perpetuate misrepresentations of nonverbal behaviors in adults with profound ID.